1994
DOI: 10.1002/jnr.490390503
|View full text |Cite
|
Sign up to set email alerts
|

Tau‐like immunoreactivity in Alzheimer and control skin fibroblasts

Abstract: The presence of the microtubule-associated protein tau in skin fibroblasts derived from Alzheimer patients and normal controls was investigated using a panel of well-characterized anti-tau antibodies against epitopes spanning the tau protein from the amino to the carboxyl end. The antibodies immunolabeled a fine, fibrillar cytoplasmic network in all skin fibroblasts. Disruption of the microtubule network with colchicine did not affect the immunolabeling of the fibrillar network nor did treatment with cytochala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The microtubule-associated protein (MAP) tau is mainly found in the brain and spinal cord, but is also found at relatively high levels in heart, skeletal muscle, lung, kidney and testis and at much lower levels in adrenal gland, stomach, liver, spleen and fibroblasts (Montejo et al 1986;Tucker 1990;Ashman et al 1992;Lee and Rook 1992;Lubke et al 1994;Matsuyama and Bondareff 1994;Gu et al 1996). Tau is highly enriched in axonal compartments (especially in mature neurons; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The microtubule-associated protein (MAP) tau is mainly found in the brain and spinal cord, but is also found at relatively high levels in heart, skeletal muscle, lung, kidney and testis and at much lower levels in adrenal gland, stomach, liver, spleen and fibroblasts (Montejo et al 1986;Tucker 1990;Ashman et al 1992;Lee and Rook 1992;Lubke et al 1994;Matsuyama and Bondareff 1994;Gu et al 1996). Tau is highly enriched in axonal compartments (especially in mature neurons; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although process extension was not directly examined in this previous study, it is therefore likely that the formation of cellular processes by ras-transformed cells does not require increased expression levels of tubulin or microtubule-associated proteins. Similarly, although recent studies have shown that proteins with antigenic similarity to neuronal tau are expressed by fibroblasts [Ingelson et al, 1996;Matsuyama and Bondareff, 1994], these proteins are expressed in fibroblasts only at low levels and their function in this cell type has not been determined. Higher expression levels of the microtubule-associated protein MAP4 are expressed in fibroblast [Bulinksi and Borisy, 1980], and MAP4 could therefore play a role in stabilizing microtubules within processes observed in the present study.…”
Section: Process Extension Mechanisms Are Similar In Different Cell Typesmentioning
confidence: 99%
“…Proposed functions for peripheral tau include transcriptional involvement in leukocytes and regulation of signal transduction in a neuroblastoma cell line [10,11]. Presence of tau has also been demonstrated in human fibroblasts [9,12,13] but tau levels in fibroblast lysates from individuals with AD were not elevated compared to controls [9], indicating that disturbed metabolism of tau in AD probably is CNS specific.…”
Section: Introductionmentioning
confidence: 99%